Medical-legal partnerships: An integrated approach to advance health equity and improve health outcomes for people living with HIV - Martinez, Omar; Munoz-Laboy, Miguel; Davison, Robin (Frontiers in Reproductive Health, 2022)
Medical Legal Partnerships (MLPs) offer a structural integrated intervention that could facilitate improvements in medical and psychosocial outcomes among people living with HIV (PLWH). Through legal aid, MLPs can ensure that patients are able to access HIV services in a culturally sensitive environment. We conducted organizational-level qualitative research rooted in grounded theory, consisting of key informant interviews with MLP providers (n = 19) and members of the Scientific Collaborative Board (SCB; n = 4), site visits to agencies with MLPs (n = 3), and meetings (n = 4) with members of the SCB. Four common themes were identified: (1) availability and accessibility of legal and social services support suggest improvements in health outcomes for PLWH; (2) observations and experiences reveal that MLPs have a positive impact on PLWH; (3) 3 intersecting continua of care exist within MLPs: HIV care continuum; legal continuum of care; and social services continuum; and (4) engagement in care through an MLP increases patient engagement and community participation. The MLP approach as a structural intervention has the potential to alleviate barriers to HIV/AIDS treatment and care and thus dramatically improve health outcomes among PLWH.